The Effect of Atenolol on CK-MB Levels in Hypertensive Patients - Inaam A. Amin (College of Pharmacy University of Baghdad, 2017)
Atenolol is one of beta-adrenergic receptor blocking agent. It is widely used for the treatment of hypertension as a selective antihypertensive drug. But long term usage of atenolol may cause one of the cardiovascular diseases like myocardial infarction. To prove the relationship between atenolol and cardiovascular disease, measurement of creatinekinase-MB as a diagnostic indicator in early and long term usage of this drug by hypertensive patients is recommended.  A comparative study was conducted in Al-Yarmouk Teaching Hospitalâ€"Emergency Department- on 30 hypertensive patients using atenolol. They were divided into (2) groups A and B according to the duration of the drug usage. Group A- (15) patients with a mean age (56+6) years. They used atenolol for a period of (1-5) years. Group B- also (15) patients with mean age (60+6) years. They used atenolol for (6-20) years. Both groups were with nearly the same number of males and females. All subjects of the study groups were screened to exclude evidence of hyper or hypothyroidism, diabetes and chronic renal failure. Venous blood samples were taken in first 8 hours after onset symptoms of cardiac attack from each patients and the levels of creatine kinase-MB were estimated and compared between the (2) groups. There is a significant correlation between levels of serum creatine kinase-MB of group A and group B (P<0.05). Atenolol causes increased level of serum CK-MB and this increase was directly proportional to the duration of the drug usage. CK-MB is one of cardiac markers that released from heart muscle when it is damaged as a result of myocardial infraction. So, atenolol has a significant correlation with development of myocardial diseases. Key words:  hypertension ,  Atenolol  and  side  effects ,  creatine kinase-MB ,  Atenolol antihypertensive.